Examining collaborative leadership through interprofessional education: findings from a mixed methods study. Issue 2 (4th March 2019) - Iachini, Aidyn L.; DeHart, Dana D.; Browne, Teri; Dunn, Brianne L.; Blake, Elizabeth W.; Blake, Christine
ABSTRACT: Collaborative leadership is essential as recent trends in healthcare service delivery necessitate interprofessional collaboration and care. Interprofessional education (IPE) efforts, therefore, have to prepare students for this type of leadership. The purpose of this study was to understand how students' perceptions of leadership change as a result of embedding a collaborative leadership model, the Social Change Model (SCM) of leadership, in an IPE course. Data were collected from 30 students participating in an interprofessional course through two interprofessional course reflections, pre/post leadership posters and poster reflections, and a pre/post survey. Results from paired sample t-tests suggested students significantly improved in their perceptions of leadership efficacy. These data also indicated improvements to the three group-level values of the SCM: collaboration, common purpose, and controversy with civility. Findings from the qualitative data suggest that students learned to view leadership as more of a team effort than the actions of a single individual and as more of a process than a role. Findings also revealed the benefits and challenges of using a visual process of poster development as a way of examining students' changes in perceptions of leadership over the course of the semester. Implications are discussed in relationship to the utility of the SCM in promoting students' shifts in conceptualizations of leadership that emphasizes collaboration and helps prepare students to engage in these ways within interprofessional teams in their practice.